I knew I could do this work. Seven strategies that promote women's activism and leadership in unions - Caiazza, Amy (Washington, DC, 2009)
"This report is designed to promote women's activism and leadership within unions across the country at the local, state, regional, and national levels. Based on interviews with union organizers and activists throughout the United States, the report explores theree main questions: What are the main obstacles that discourage women's union activism and leadership? How can unions help overcome them? How can women's movement organizing better support union women? The report outlines seven strategies that unions can use to encourage women's increased participation."